Strategi Bisnis Klinik Kesehatan Grhamedika Dengan Penerapan Sistem Informasi Manajemen Menggunakan Analisis SWOT - Utomo, Bangun Prajadi Cipto; Santosa, Tri Djoko (Politeknik Indonusa Surakarta, 2024)
Management Information Systems (MIS) play a crucial role in health services. In this digital era, health clinics are increasingly adopting information technology to improve efficiency, service quality and data management. In the context of the Grhamedika Health Clinic, SWOT analysis is a relevant tool for understanding the internal and external factors that influence the implementation of SIM. In this research, we will dig deeper into the strengths, weaknesses, opportunities and threats associated with implementing SIM in the clinic. With in-depth understanding, we can design the right strategy to optimize information systems and improve health services. The results of the analysis show that Grhamedika has strengths in service quality and experienced medical personnel, but is faced with weaknesses such as limited facilities and infrastructure. Opportunities for developing services through the latest medical technology and increasing public health awareness are the main focus, while intense competition in the health sector is a threat that must be overcome. The resulting strategic recommendations are expected to help Grhamedika achieve competitive advantage and meet public health needs more effectively.